Cycle time variation analysis on shop floor production line-a case study in medical device manufacturing industry - Subramaniam A/L Agilan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This is a case study of cycle time of machines and production lines of a medical device manufacturing plant. Unstable cycle times leads to unreliable production operation which in turn reduces producticity. More time, energy and money is wasted in non-value added activities. Therefore this research is done to establish strategies to improve cycle production rate of target facility.